HUTCHINSON-GILFORD PROGERIA SYNDROME: A PREMATURELY AGING DISORDER (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Hutchinson-Gilford Progeria Syndrome (HGPS) is an extremely rare genetic disorder characterized by premature aging, involving aberrant splicing of the LMNA gene, resulting in the production of a disease-causing mutant lamin A protein called progerin. Clinical manifestations are evident by the first or second year of life and include the physical characteristics usually associated with the elderly. Because neither parent carries or expresses the mutation, each case is believed to represent a sporadic, new mutation that happens most notably in a single sperm or egg immediately prior to conception. Clinical trials investigating farnesyltransferase inhibitors (FTIs), statins, and bisphosphonates as HGPS treatments are currently underway. FTIs prevent farnesylation and localization of progerin to the cell membrane but do not repair the function of the abnormal progerin protein within the cytoplasm that may result in abnormalities in cell function and DNA repair that, therefore, would not be treated with these drugs. Thus some other novel treatment strategies are required for the more effective treatment. This review summarizes the clinical characteristics of this disease, the underlying mutation in the lamin A (LMNA) gene that results in this phenotype and the recent advances in treatment strategies.